Impact of Management Discussion and Analysis - Umdiana, Nana; Evana, Einde; Metalia, Mega (Journal of Ecohumanism, 2025)
This research aims empirically test the influence management’s discussion and analysis on investor reactions and market reactions to manufacturing companies listed on the Indonesian Stock Exchange. The population in this research is all manufacturing companies listed on the Indonesia Stock Exchange (BEI). Using method purposive sampling with a research sample of 133 companies. The type and source of data in this research uses secondary data taken directly from the official website of the Indonesia Stock Exchange (BEI). The analytical method in this research uses simple linear regression analysis. The test results and discussion prove that management’s discussion and analysis has no effect on investor reactions. management’s discussion and analysis has no effect on market reactions, and partial test results show that management’s discussion and analysis has no effect on investor reactions and market reactions. In manufacturing companies listed on the Indonesian Stock Exchange.